Using an adult development model to help explain pre-service teacher resistance to learning about race. Issue 5 (2nd September 2016) - Puchner, Laurel; Markowitz, Linda
Abstract : This article shows the potential usefulness of applying Kegan's constructive-developmental model to White teacher education students' difficulties in understanding racial dynamics in US society. The data for this analysis come from a study examining the evolution of White teacher candidates' understandings and practices related to diversity as they experienced different parts of an undergraduate teacher education program over a two-semester period. We describe the case of one of the students, Michelle, focusing on the contradiction between Michelle's intense engagement, hard work and enjoyment in her required Foundations course and her simultaneous rejection of core ideas of the course. We show how Kegan's model is helpful in explaining this contradiction and discuss implications for teacher educators.